Some reproductive characteristics of female Shugor, Dubasi and Watish sheep reared at El Huda sheep research station - Suleiman, A.H. (1982)
Eighty-nine ewe lambs comprising 36 Shugor, 29 Dubasi and 24 Watish sheep weaned 16 weeks following birth experienced their first oestrus at an average age of 206 days. Winter-born ewe lambs attained sexual matrurity at a lower age than those lambs, which were born during the summer. The mean values for puberty age in the two seasons were 199.1±7.87 and 211.1±4.62, days, respectively and were significantly different at 5 percent. Puberty live weight was significantly influenced by genotype (P